A cross-subject content analysis of science textbooks using the understandings about scientific inquiry rubrics - Strippel, Christian; Tomalla, Lutz; Sommer, Katrin (Research in Subject-matter Teaching and Learning (RISTAL), 2018)
Recent empirical research has shown that students’ inquiry competence can be improved, when they are explicitly taught understandings about scientific inquiry (USI). However, there is little research on the USI content taught in high schools. Examining Science textbooks is one way of identifying what might be taught in the classroom. The aim of this paper is to analyse the content of German science textbooks regarding their USI content. To do so, the understandings about scientific inquiry rubrics (USIR) were developed, validated and applied to a sample of n = 789 texts from n = 13 German textbooks for high school science. The results show that most textbooks dedicate one specific page to USI. The breadth of statements is relatively narrow. For researchers, the USIR present an instrument for the content analysis of instruction materials and learning environments. For teachers and curriculum developers they can be used as an instrument to enrich the content of textbooks, instruction materials and presentations.